Privileges among the privileged: the effect of starting conditions at age 16 on occupational success from age 16 to 66 in an educationally privileged group - Klaus Birkelbach; Hermann Dülmer; Heiner Meulemann (Frontiers in Sociology)
IntroductionDo starting conditions in an educationally selected youth still affect occupational success in adult life? Educational selection depends on starting conditions for the career beyond the school which are given or controllable – gender, intelligence, and social origin vs. grades, aspirations, and life plans. In a group already selected, it intensifies competition and challenges motivations to succeed more strongly such that new privileges can arise among the already privileged. This is examined longitudinally from age 16 to 30, 43, 56, and 66. Two hypotheses will be tested cross-sectionally at each age: (1) Effectiveness: All starting conditions should increase occupational success, (2) Control force: Given starting conditions have less impact than controllable ones. And two hypotheses will be tested longitudinally from age 30 to 66: (3) Tapering off: All starting conditions lose impact. (4) Control persistency: Given conditions lose more impact than controllable ones.MethodsData are from the Cologne High School Panel (CHISP). It starts off with 3240 German Gymnasium (the highest layer of the three German high school forms) students at age 16 in 1969. They have been re-interviewed at age 30, 43, 56, and 66 when 1013 respondents remain. The occupational career success from 16 to 66 is measured as occupational prestige and hourly net income, corrected for inflation.ResultsThe results show that prestige is higher for men than women; it increases with social origin, and aspirations to a strong degree at age 30, to a lesser degree at age 43, to a still lesser degree at age 56, and not at all at age 66; however, the impact of the earlier success increases strongly and continuously. In brief, the past fades away and the careers consolidate. But given conditions do not have weaker impacts than controllable ones and do not lose their impact more strongly. Thus, (1) the effectiveness hypothesis is confirmed for most starting conditions, but (2) the control force hypothesis is not; and (3) the tapering off hypothesis is, but (4) the control persistence hypothesis is not. Given starting conditions have no less power over occupational success than controllable ones. Privileges resonate indiscriminately and decreasingly in life histories.DiscussionIncome at age 30, 43, 56, and 66 does not increase continuously with any starting condition, but decreases with intelligence at age 30 and increases with male gender and having a life goal at age 43. And the impact of the earlier successes increases strongly and continuously. In brief, the past throws no shadow and the careers consolidate. The (1 and 2) effectiveness and the control force hypothesis are disconfirmed. Given the irregular impacts of starting conditions, (3 and 4) the fading off and the control persistency hypothesis cannot be meaningfully examined. Privileges do not continue to favour the privileged and occupational careers stabilize autonomously.